2022
DOI: 10.4143/crt.2021.835
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Cancer Recurrence and Its Negative Impact on Health-Related Quality of Life in Long-term Breast Cancer Survivors

Abstract: Fear of cancer recurrence (FCR) is a common psychological issue in breast cancer (BC) survivors during early survivorship but whether the same is true among long-term survivors has yet to be empirically evaluated. This study investigated FCR level, its associated factors, and impact on quality of life (QoL) in long-term BC survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Apart from examining its trajectory at specific time points, the impact of FCR on QOL in patients with lung cancer has rarely been explored. Current research on the impact of FCR on QOL in patients with cancer has primarily focussed on breast cancer (Schapira et al, 2022;Tran et al, 2022), gynaecological cancer (Tsai…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from examining its trajectory at specific time points, the impact of FCR on QOL in patients with lung cancer has rarely been explored. Current research on the impact of FCR on QOL in patients with cancer has primarily focussed on breast cancer (Schapira et al, 2022;Tran et al, 2022), gynaecological cancer (Tsai…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…However, insufficient attention has been paid to patients with lung cancer with high risks of recurrence and metastasis. Most research is done using cross-sectional studies to explore FCR in patients with cancer (Simard et al, 2010;Tran et al, 2022) and focuses on assessing FCR levels and identifying influencing factors at specific time points.…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study demonstrated that a symptom cluster of anxiety, depression, fatigue, and pain adversely affected the QOL of women with breast cancer who were receiving radiotherapy or chemotherapy for this disease [9]. Evidence suggests that breast cancer survivors at any stage often experience fear of cancer recurrence, which may negatively affect their QOL [10,11]. Another study revealed that breast cancer survivors with depressive symptoms tend to have lower treatment adherence than those without such symptoms [12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the initial diagnosis, the recurrence of breast cancer is a destructive and very distressing event for the sufferers, and although they expected the initial treat-ment to destroy and control the proliferation of all malignant cells, they face the return of cancer again (6). And this has caused most of the survivors of primary breast cancer to worry and fear and have negative emotional feelings in most of the survivors of early breast cancer (7).…”
mentioning
confidence: 99%